A comprehensive design for prevention and management of COVID-19 in a tertiary medical institution in Bangladesh - Chitto Ranjan Debnath; Md Saiful Islam Khan; Md Sakirul Islam Khan; Proggananda Nath; Lakshmi Narayan Majumder; Md. Sayem Monowar; Monalisa Khan; Farzana Islam; Hiroaki Nabeka; Tetsuya Shimokawa; Seiji Matsuda; Mamun Al Mahtab; et al. (Journal of Infection in Developing Countries)
Introduction: Containment of the further spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and reducing fatality due to coronavirus disease 19 (COVID-19) represent a pressing challenge to global health services. Here, we present a management blueprint for both the containment of SARS-CoV-2 and treatment of COVID-19 through a comprehensive approach.